SISTEM PENDUKUNG KEPUTUSAN PENENTUAN OBYEK WISATA BERBASIS ANP DENGAN TAMPILAN PETA - , NOOR ALAM HADIWIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Beside as known as city of struggle, cultural and education center, Yogyakarta is, up now, also know with its rich natural and cultural potency and still becomes a well known tourist destination in Indonesia and International. With varied touristâs destination, it is precise in using decision support system on tourist object resolve. In the research, the decision of criteria and sub criteria are conducted with survey and in depth interview with Tourism Service of DIY Province and Tourism Study Center of Gadjah Mada University. Later on, those criteria and sub criteria are given the paired comparison measurement with preference between 1-9, which is converted into pairwise comparison matrix form. The finding obtained by using Analytic Network Process (ANP) approach in the resolve of tourism attraction based on criteria and each sub criteria can be determined the best tourism object alternative and some existing alternatives according to the rank. Then, the method of ANP in the consistency measurement of each criteria, subcriteria, inner and outer dependence can accommodate inconsistency in the research. Keyword: Decision Support System, Analytic Network Process (ANP), Tourism Attraction.